2020
DOI: 10.3389/fpsyg.2020.00967
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Activity and Emotional Intelligence in College Students: The Mediating Role of Self-Efficacy

Abstract: Background: College students are an inexhaustible driving force for social development, and college students with good physical and psychological qualities can better adapt to changes in the external environment. The purpose of this study was to explore the intrinsic relationship of physical activity and emotional intelligence among college students and to determine the primary role of self-efficacy in their relationships.Methods: Eight hundred thirty-five college students from two comprehensive universities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
7
45
4
1
Order By: Relevance
“…The positive impact of PA on self-efficacy in the study is not surprising, and the finding is in line with the previous studies [ 29 , 30 , 31 ]. Also being consistent with the existing literature, self-efficacy has a negative impact on AP [ 11 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The positive impact of PA on self-efficacy in the study is not surprising, and the finding is in line with the previous studies [ 29 , 30 , 31 ]. Also being consistent with the existing literature, self-efficacy has a negative impact on AP [ 11 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Research has found that PA was positively related to self-efficacy in adolescents and older adults [ 28 , 29 , 30 ]. The positive relationship between PA and self-efficacy was also found in college students, and the higher PA intensity, the higher level of self-efficacy [ 31 ]. Additionally, different formats of PA such as aerobic exercise, resistance training, or mind-body technique (e.g., Yoga, Tai Chi) could also enhance self-efficacy [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activities performed at different intensities have a significant effect on self-efficacy as shown in a study conducted on high school students (Zhao et al, 2019). Unlike the findings of our study, Wang et al (2020) found that the self-efficacy of senior university students is low, adding that the reason for this is the anxiety of finding a job after graduation.…”
Section: Discussioncontrasting
confidence: 99%
“…This is possible because of the general cultural structure of Turkish society, in which socio-cultural factors are effective depending on the social role of men, and men take a more active role in social life. The literature review shows that the results of Özkara ( 2019), Atasoy and Aktaş (2020), and İrmiş and Barutçu (2012) overlap the results of this study in terms of entrepreneurship while the results of Wang et al (2020) overlap the results of this study in terms of self-efficacy…”
Section: Discussionsupporting
confidence: 53%
“…As the extension of the concept of health literacy, mental health literacy has similar functions, which could increase the level of physical activity in students through improving the in-depth understanding of perceived exercise benefit (15,20). Addition, past researches that have revealed self-efficacy may not always directly affect physical activity, instead acting in conjunction with behavioral capability (knowledge and/or skill) variables, such as health literacy (26,46). Furthermore, higher health literacy levels strengthened the positive relationship between self-efficacy and health behaviors (47).…”
Section: Discussionmentioning
confidence: 99%